The effect of modified atmospheres on the saw-toothed grain beetle Oryzaephilus surinamensis (L.)(Coleoptera: Silvanidae) and the quality of semi-dried dates. (September 2021) - Hashem, Mohamed Y.; Khalifa, Elham A.; Ahmed, Sayeda S.
Abstract: The saw-toothed grain beetle Oryzaephilus surinamensis plays a major role in reducing the quality and volume of dried fruits. The aim of this study was to evaluate the effect of modified atmospheres (MAs) enriched in CO2 or N2 at 25 °C and 35 °C on the adult and larval stages of O. surinamensis and dried date quality. The tested MAs containing 20%, 30%, 40%, and 50% CO2 and the MAs containing 97% and 98% N2, with different exposure periods were performed in the laboratory at 25 °C or 35 °C ± 2 °C, 65% ± 5% r.h and photoperiod of 16 Light:8 Dark. The adults and larvae were found to be more susceptible to CO2 or N2 at 35 °C than those at 25 °C. Both adults and larvae reached 100% mortality after 4–6 days exposure to 20%–50% CO2 at 25 °C and 3–5 days exposure to the same concentrations at 35 °C. The mortality reached 100% after 2–3 days when adults were exposed to 97% or 98% N2 at 35 °C, but the larvae reached the complete mortality after 5 and 4 days exposure to 97% and 98% N2, respectively, at 35 °C. The adult stage was more susceptible than the larval stage to MAs enriched in CO2 or N2 . Also, the results showed that an MA containing 50% CO2 and another containing 98% N2 led to increased total carbohydrates, protein, fat, and ash in treated dates compared to control dates. MAs at high temperatures may be recommended to control O. surinamensis populations in dried date stores due to the advantage of a short duration treatment capable of killing larvae and adult stages of this insect, with positive effects on dried fruit quality. Highlights: Modified atmospheres (MAs) affected O. surinamensis and dried date quality. MAs were more effective on adults and larvae at 35 °C than 25 °C. Both adults and larvae stages reached the complete mortality after 3–6 days. LT values indicated that the adults are more susceptible than the larvae. MAs containing 50% CO2 or 98% N2 affected the dried date quality.